PENGARUH MEDIA PEMBELAJARAN POP-UP BOOK TERHADAP HASIL BELAJAR IPAS SISWA KELAS IV UPTD SD NEGERI 122379 PEMATANGSIANTAR - Situmorang, Jennifier Lorensa; Simanjuntak, Bernard; Napitupulu, Rio Parsaoran (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
This study aims to determine the influence of Pop-Up Book learning media on the learning outcomes of Natural and Social Sciences (IPAS) of grade IV students at UPTD SD Negeri 122379 Pematangsiantar. The Pop-Up Book media was chosen because it can present material visually, interactively, and interestingly, so that it is expected to be able to increase students’ understanding and interest in learning. The type of research used is quantitative with experimental methods, using a pre-experimental design in the form of One Group Pretest-Posttest Design. The research sample amounted to 25 grade IV students who were selected in total sampling. The data collection technique used multiple-choice tests administered before and after treatment. The results of data analysis showed that there was a significant increase in student learning outcomes after the use of Pop-Up Book media. The results of the hypothesis test showed that the t_hitung value of 26.131 was greater than the t_tabel of 2.064 (t_hitung > t_tabel), so that H₀ was rejected and Hₐ was accepted. These findings show that the use of Pop-Up Book media has a positive influence on students’ social studies learning outcomes. In addition, this media also increases students’ active involvement in the learning process and assists teachers in delivering material in a more varied and fun way. Based on these results, it is recommended that teachers consider the use of Pop-Up Book media as an alternative in improving the quality of social studies learning in elementary schools